Detection of persistent forms of Borrelia burgdorferi sensu stricto in infected mice after antibiotic treatment - Ramzy, Ida (Jihočeská univerzita, 2020)
Antibiotic treatment of Lyme disease is a challenging procedure with unexpected outcomes that may arise sometime. According to standard protocols recommended by the Centers for Disease Control and Prevention, USA (CDC) for early Lyme disease, a short course of oral antibiotics cures the majority of cases. This thesis deals with the analysis of the efficiency of 2 majorly used antibiotics, doxycycline and amoxicillin, in elimination of Borrelia infection on laboratory mice model after 2 weeks of treatment. Our results confirmed the presence of persistent forms of spirochetes in mice tissues after antibiotic treatment using the spirochete cultivation method in liquid MKP medium.
Detection of persistent forms of Borrelia burgdorferi sensu stricto in infected mice after antibiotic treatment
Keywords: Lyme disease; Borrelia burgdorferi; doxycycline; amoxicillin; spirochetes; parasitology; chronic Lyme disease; Lyme disease; Borrelia burgdorferi; doxycycline; amoxicillin; spirochetes; parasitology; chronic Lyme disease; antibiotics